Revitalizing Traditional Crafts: Bridging Cultural Heritage and Innovation in Indonesia's Creative Economy - Hendriyana, Husen; Rachmadi, Gustiyan; Kudya, Komar; Jahada, Caraka Aji Puja (Institut Seni Indonesia Denpasar, 2025)
The revitalization of traditional crafts represents a strategic approach to strengthening Indonesia’s creative economy, which is deeply rooted in its rich cultural heritage. This article examines the dynamic interplay between the preservation of traditional values and the pursuit of innovation, aiming to bridge the past and future within the practices of the creative economy. Employing a qualitative approach within an interpretative-critical paradigm, the study investigates the intersection of tradition and innovation. Design Thinking serves as the methodological framework for exploring how sustainable innovation can emerge from local cultural traditions while responding to global market demands. In the initial phase, a practice-based research methodology is utilized to uncover the fundamental values embedded in traditional Indonesian artefacts. Building on these insights, a practice-led research approach is then employed to develop a design model that translates traditional knowledge into applicable strategies for creating innovative works. In this context, practice-based research focuses on the creation of artefacts as a primary method of generating knowledge, while practice-led research emphasizes the development of new theoretical understandings through creative practice. The findings suggest that revitalization efforts grounded in local cultural values can foster a sustainable creative ecosystem, strengthen national identity, and stimulate community-based economic growth. These results underscore the importance of synergy among creative practitioners, government institutions, and local communities in shaping an inclusive and culturally grounded future for Indonesia's creative industries.